NESZ effects on wind retrievals from Gaofen-3 SAR wave mode data - Ren, Lin; Dai, Jinyuan; Yang, Jingsong; Jiang, Chong; Zheng, Gang; Chen, Peng; Li, Xiaohui (Frontiers in Earth Science, 2024)
This study analyzes the effects of noise equivalent sigma zero (NESZ) on wind retrieval accuracy based on the estimated NESZ and wind retrievals from Gaofen-3 (GF3) synthetic aperture radar (SAR) wave mode data. The NESZ was estimated from the normalized radar cross-section (NRCS) bottom envelope from the calm sea (winds <1 m/s). The data used included GF3 SAR wave mode data, collocated NOAA/NCEP Global Forecast System (GFS), Advanced Scatterometer (ASCAT) and National Data Buoy Center (NDBC) buoy wind data. First, the GF3 data were recalibrated using a numerical weather prediction method in which the recalibration coefficients at four polarizations and different incidence angles were estimated. The NESZ trends were then estimated along with the in-orbit time and incidence angles based on the recalibrated GF3 NRCS. NESZ trends show no obvious change with in-orbit time, whereas it shows significant fluctuations with the incidence angle. Moreover, wind speed and direction were retrieved by the CMOD5.N model using the optimal scheme (for co-polarized data, VV, and HH data) and a linear model (for cross-polarized data, VH, and HV data). The wind retrieval accuracy was estimated by comparison with ASCAT and NDBC winds. Finally, the wind retrieval accuracy with the NESZ for different incidence angle bins was analyzed. The root mean square error (RMSE) of the wind speed and direction increase with the NESZ for each polarization. For the NESZ effects, the co-polarized data are more evident than the cross-polarized data for wind speed retrieval, whereas the two co-polarized data are close for wind direction retrieval. When the NESZ increases from −41 dB to −29 dB, there is a wind speed RMSE degradation of 1.5 m/s, 1.2 m/s, 0.7 m/s and 0.5 m/s for VV-, HH-, VH-, and HV-polarized data respectively, while there is a wind direction RMSE degradation of 5o for co-polarized data. This reveals the necessity of reducing the SAR NESZ to improve wind retrieval accuracy.